Changing the philosophy of organization management in the times of e-economy = Zmiana filozofii zarządzania organizacją w dobie gospodarki elektronicznej - Bieńkowska, Jolanta; Sikorski, Czesław (Zielona Góra: Faculty of Economics and Management Press)
The paper highlights the fundamental changes in the way of thinking in science and the management practice caused by the transition from the era of industrial civilization to the information civilization. These include the change in the subject of management, i.e. the transition from the management of the organization to the management of joint projects; from the requirement of flexibility from own resources to the ability to use external resources and the departure from the methodological rationality of a decision to the material rationality.
Keywords: zarządzanie; organizacja; projekt; rynek elektroniczny; hiperelastyczność; podejmowanie decyzji; racjonalność; management; organization; project; electronic market; hyperflexibility; rationality; decision-making process